Translation and validation of Warmometer, a tool for assessing warmth in patient-provider relationships, for use in Brazilian Portuguese - Brooke, Marieta Sodré; Nakamura, Mary Uchiyama; Hosomi, Jorge Kioshi; Ribeiro, Meireluci Costa; Sass, Nelson (São Paulo Medical Journal, 2018)
BACKGROUND: Empathy in the patient-provider relationship is associated with important outcomes in healthcare practice. Our aim was to translate and validate Warmometer, a visual tool for assesing warmth in patient-provider relationships, for use in Brazilian Portuguese. DESIGN AND SETTING: Cross-sectional study conducted at an antenatal clinic of a public university hospital in São Paulo, Brazil. METHODS: The instrument was translated into Brazilian Portuguese and culturally adapted. It was tested for reliability and validity among 32 pregnant women, between June 2015 and January 2016. To assess construct validity, it was correlated with the Consultation and Relational Empathy (CARE) scale (gold standard for patient-provider relationships) and the Interpersonal Reactivity Index (IRI). RESULTS: The translated version of Warmometer had good face and content validity, low intra-observer reproducibility (intraclass correlation coefficient, ICC: 0.224; 95% confidence interval, CI -0.589 to 0.621; P = 0.242) and high inter-observer reproducibility (ICC: 0.952; 95% CI 0.902 to 0.977; P < 0.001). There was a strong correlation between Warmometer and CARE (r = 0.632) and a weak correlation between Warmometer and IRI (r = 0.105). CONCLUSIONS: Warmometer was translated, culturally adapted and validated for use in Brazilian Portuguese. The translated version is a reliable tool for assessing the degree of empathy perceived by the patient in a patient-provider relationship.